The arrest : a novel - Lethem, Jonathan (Ecco, an imprint of HarperCollinsPublishers, 2020)
Working as an organic farmer in a near-future world devoid of technology, a former Los Angeles screenwriter unexpectedly reconnects with his once-famous partner, who has retrofitted a nuclear-powered digger to launch an unknown agenda.